EDUKASI UPAYA MENINGKATKAN IMUNITAS TUBUH PADA ANAK - Fikriah, Wasiatul; Sumiyati, Etty; Mahayu Prawati, Ni Putu Dinda; Wastian Septiant, Ruvita; Yuswantina, Richa; Mardiyanti, Devi (Jurnal Edukasi Pengabdian Masyarakat, 2025)
Implementation of the Community Service Program, in 2024 will be carried out at SDN 01 Nyatnyono, Pabatan, Nyatnyono, Kec. West Ungaran, Semarang Regency, Central Java. With various activities that we carry out, namely educating about efforts to increase body immunity in elementary school children at SDN Nyatnyono 01 as well as distributing Vitamin C and Honey to students to maintain health. The method used uses interactive methods that can improve critical thinking skills, such as group discussions, role plays, or case studies. In this case, a role play is used where there are question and answer activities such as posttest and pretest regarding body immunity, where it is hoped that students can participate actively in this activity. The results of the activity stated that all the children at SD Nyatnyono 01 before education had a fairly good level of knowledge, and after exposure to educational material they had a very good level of knowledge. In this way, participants are able to understand the material that has been presented and the activities that have been carried out can increase the knowledge of the children of Nyatnyono 01 Elementary School regarding Efforts to Increase Body Immunity in Children. Keywords: Education; Immunity; Vitamin C; Honey